Penggunaan Video Tutorial sebagai Model Pembelajaran Menulis Puisi bagi Siswa SMA di Masa Pandemi Virus Corona - Alfiati Alfiati (An-Nuha : Jurnal Kajian Islam, Pendidikan, Budaya dan Sosial, 2020)
Video tutorials are videos that are presented by a teacher to deliver learning material. These video tutorials are often also known as learning videos. The advantages of video tutorials compared to other learning media are as follows. First, video tutorials are very clear in demonstrating a phenomenon and the procedures involved in a movement. Second, video tutorial users can speed up and slow down the tutorial video movements so that the material presented is clearer. Third, video tutorials can use animation to illustrate abstract and moving material. Fourth, video tutorials can attract students' attention and interest through moving images, audio, and text media. Apart from the advantages of video tutorials, there are also disadvantages. The weakness of video tutorials lies in the production process which requires special skills and is relatively expensive. The use of video tutorials during the corona virus pandemic can complement online learning tools. Teachers can use video tutorials as discussion material, practical material, and increase students' understanding of the material presented through online meetings